Peran Media Sosial TikTok Sebagai Strategi Digital Marketing dalam Meningkatkan Brand Awareness dan Loyalitas Konsumen - Widya Afrida; Pristiyono Pristiyono; Syukron Arjuna (Universitas Proklamasi 45, 2026)
This study examines how TikTok can be used as a digital marketing medium to increase brand awareness and customer loyalty. TikTok is a popular platform due to its interactive video content that can be customized to user preferences. Quantitative methods were used in this study, involving a survey of fifty active TikTok users in Rantauprapat. Purposive sampling was the sampling method. Data processing was carried out using SPSS with several tests. The results of this study will show that TikTok directly and through intermediary variables influences brand awareness and customer loyalty.